2009
DOI: 10.1024/0301-1526.38.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic vertebral artery aneurysm following blunt suboccipital trauma

Abstract: Traumatic vertebral artery (VA) injury has been neglected and mistaken to be innocuous. Herein, we present a rare case with a as subarachnoid hemorrhage (SAH) following blunt suboccipital trauma. Initially, it was mistaken as a saccular aneurysm and was just coincident with traumatic SAH. Surgical clipping was performed by our senior neurosurgeon and looked secure. But massive bleeding occurred before complete closure of the dura wound. Opening the wound again, blood gushed out from the junction of the aneurys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Delayed deterioration in consciousness and headache at day 8 due to bleed from VA TICA Left vertebral 8 At second presentation after TICA rupture on day 8 No DSA at day 1 (occlusion) and day 8 (TICA) Clipping after bleed from new TICA post coiling Yes No deficits at 1 year Hydrocephalus not needing permanent CSF diversion Cohen et al, 2010 [ 13 ] 23 Direct neck trauma during taekwondo Acute drop in conscious level Left vertebral 1 Yes No DSA at day 1 Endovascular vessel occlusion Yes Mild dizziness and ataxia at 1 month Hydrocephalus not needing permanent CSF diversion Coulter et al, 2011 [ 14 ] 20 Road traffic accident Acute drop in conscious level Right vertebral 1 Yes No DSA at day 1 Endovascular vessel occlusion No No deficits No Purgina et al, 2015 [ 15 ] 22 Assault Loss of consciousness with improvement. Acute deterioration in consciousness at day 9 due to rebleed Left PICA 7 Yes Yes, day 1 DSA negative, CTA at day 7 positive DSA at day 1 normal, CTA at day 7 small PICA aneurysm, DSA at day 9 enlarged PICA aneurysm Too unstable for treatment No Death Rebleed and hydrocephalus Morard & deTribolet, 1991 [ 16 ] 31 Fall Acute drop in conscious level Right PICA 10 Yes No DSA at day 10 Clipping Yes Full recovery Hydrocephalus requiring shunt Chiang et al, 2009 [ 17 ] 50 Assault Acute drop in conscious level Right vertebral 1 Yes No …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed deterioration in consciousness and headache at day 8 due to bleed from VA TICA Left vertebral 8 At second presentation after TICA rupture on day 8 No DSA at day 1 (occlusion) and day 8 (TICA) Clipping after bleed from new TICA post coiling Yes No deficits at 1 year Hydrocephalus not needing permanent CSF diversion Cohen et al, 2010 [ 13 ] 23 Direct neck trauma during taekwondo Acute drop in conscious level Left vertebral 1 Yes No DSA at day 1 Endovascular vessel occlusion Yes Mild dizziness and ataxia at 1 month Hydrocephalus not needing permanent CSF diversion Coulter et al, 2011 [ 14 ] 20 Road traffic accident Acute drop in conscious level Right vertebral 1 Yes No DSA at day 1 Endovascular vessel occlusion No No deficits No Purgina et al, 2015 [ 15 ] 22 Assault Loss of consciousness with improvement. Acute deterioration in consciousness at day 9 due to rebleed Left PICA 7 Yes Yes, day 1 DSA negative, CTA at day 7 positive DSA at day 1 normal, CTA at day 7 small PICA aneurysm, DSA at day 9 enlarged PICA aneurysm Too unstable for treatment No Death Rebleed and hydrocephalus Morard & deTribolet, 1991 [ 16 ] 31 Fall Acute drop in conscious level Right PICA 10 Yes No DSA at day 10 Clipping Yes Full recovery Hydrocephalus requiring shunt Chiang et al, 2009 [ 17 ] 50 Assault Acute drop in conscious level Right vertebral 1 Yes No …”
Section: Resultsmentioning
confidence: 99%
“…A retrospective series of 130 patients with blunt head trauma and SAH demonstrated that only 8 % of SAH related to head injury resulted from congenital aneurysm rupture [ 28 ]. SAH from a traumatic posterior circulation TICA may therefore be initially misdiagnosed as aneurysmal SAH [ 17 ]. With a history of trauma and cisternal SAH identified on CT scans, vascular imaging is usually undertaken (CTA and/or DSA) during hospital admission.…”
Section: Discussionmentioning
confidence: 99%